Testing Exhaust Emissions of Plug-In Hybrid Vehicles in Poland - Jacek Pielecha; Wojciech Gis (Energies)
The article addresses the usage patterns of plug-in hybrid vehicles (PHEVs) under Polish conditions. The conventional approach to operating such vehicles assumes that they are used with a fully charged battery at the start. However, the economic circumstances of Polish users often do not allow for daily charging of vehicles from the domestic power grid. As a result, these vehicles are used not only in a mode powered solely by the internal combustion engine but also in a mode where the internal combustion engine is primarily utilized to charge the battery. An analysis was conducted on various ways of operating plug-in vehicles, evaluating not only harmful emissions but also fuel consumption (for battery states of charge: SOC = 100%, SOC = 50%, SOC = 0%, and SOC = 0 → 100%—forced charging mode). The study focused on the most characteristic vehicle segment in Poland, SUVs, and employed a methodology for determining exhaust emissions under real-world driving conditions. Results indicate that forced charging of such a vehicle’s battery leads to over a 25-fold increase in carbon dioxide emissions (fuel consumption) in urban areas compared to operating the vehicle with a fully charged battery (CO—25× increase, NOx—12× increase, PN—11× increase). Operating a plug-in SUV without charging it from the power grid results in a 13-fold increase in fuel consumption compared to using the vehicle with a fully charged battery (CO—10× increase, NOx—6× increase, PN—4× increase). The emission results were used to evaluate Poland’s charging infrastructure in the context of PHEV usage. The current state of the infrastructure and its development plans for 2030 and 2040 were analyzed. It was found that significant reductions in fuel consumption (by approximately 30%) and CO2 emissions are achievable by 2040. Emissions of CO, NOx, and PN are expected to decrease by about 10%, primarily due to the internal combustion engine operating at high load conditions in non-urban or highway scenarios.